Adrenal Medullary Grafts Restore Olfactory Deficits and Catecholamine Levels of 6-OHDA Amygdala Lesioned Animals. (1993) - Fernández-Ruiz, Juan; Guzmán, Rubén; Martínez, María Dolores; Miranda, María Isabel; Bermúdez-Rattoni, Federico; Drucker-Colín, René
Abstract : Aside from motor and cognitive deficits, Parkinson patients also manifest a little-studied olfactory deficit. Since in Parkinson's disease there is a dopamine depletion of the amygdala due to mesocorticolimbic system degeneration, we decided to test olfactory and taste performance of 6-OHDA amygdala lesioned rats, as well as the possible restoration of either function with adrenal medullary transplants. Two 6-OHDA lesioned groups and one control group were tested in the potentiation of odor by taste aversion paradigm. On taste aversion none of the groups showed any impairment. In contrast, the 6-OHDA lesioned rats showed a marked impairment in olfactory aversion. At this point, one of the lesioned groups received a bilateral adrenal medullary graft within the lesioned area. After two months, all groups were submitted again to the behavioral paradigm. Taste remained unaffected, but the lesioned only group did not recover either olfactory aversion or normal catecholamine levels. The grafted group, on the other hand, restored olfactory aversion and catecholamine levels. It can be concluded from this study that catecholamine depletion of the amygdala is sufficient to produce a selective olfactory deficit, not accompanied by taste impairments, and that such a deficit can be reversed by adrenal medullary transplants, which in turn restore catecholamine levels.